Allele frequency of pathogenic variants causing acid sphingomyelinase deficiency and Gaucher disease in the general Japanese population - Shuhei Sako; Kimihiko Oishi; Hiroyuki Ida; Eri Imagawa (Human Genome Variation)
Abstract Acid sphingomyelinase deficiency (ASMD) and Gaucher disease (GD) are lysosomal storage disorders associated with hepatosplenomegaly and thrombocytopenia. The incidences of ASMD and GD are known to be particularly high in the Ashkenazi Jewish population. Conversely, the number of reported patients with these diseases has been limited in Asian countries, including Japan. Here, we reviewed the allele frequencies of pathogenic variants causing ASMD and GD in the Japanese population and populations with various ancestry backgrounds using the Japanese Multi-Omics Reference Panel 54KJPN and the Genome Aggregation Database v4.0.0. The estimated carrier frequencies of ASMD- and GD-related variants were 1/180 and 1/154 in Japanese individuals, equivalent to disease occurrence frequencies of 1/128,191 and 1/94,791 individuals, respectively. These frequencies are much higher than previously expected. Our data also suggest that there are more patients with a milder form of ASMD and nonspecific clinical findings who have not yet been diagnosed.